Hydrotalcite-based composite oxide catalyst, preparation method and application of hydrotalcite-based composite oxide catalyst in preparation of alkynol

By using hydrotalcite-based composite oxide catalysts, the problems of complex catalyst preparation, large amount and long reaction time in the existing alkynol synthesis methods are solved, and efficient and economical alkynol synthesis is achieved, with high catalytic efficiency, good selectivity and short reaction time.

CN119608144APending Publication Date: 2025-03-14SHANDONG NHU PHARMA +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411610105.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the existing alkynol synthesis methods, the catalyst preparation is complex, the amount is large, and the reaction time is long, which affects the production efficiency and cost.

Method used

The hydrotalcite-based composite oxide catalyst is used, and the molecular formula of the catalyst is XxMg0.7-xAl0.2-yYyO, where X is selected from Ca, Sr, Ba, Y is selected from Ga, In, Tl, 0.02≤x≤0.05, 0.02≤y≤0.05, and the catalyst is prepared by a simple preparation method.

Benefits of technology

The synthesis of highly efficient catalytic alkynol is achieved, with high catalytic efficiency, good selectivity, a yield of up to 99.3%, a short reaction time of only 15 to 35 minutes, and a high stability of the catalyst and a cheap price, which reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130719130000011
    Figure BDA0005130719130000011
  • Figure BDA0005130719130000021
    Figure BDA0005130719130000021
  • Figure BDA0005130719130000031
    Figure BDA0005130719130000031
Patent Text Reader

Abstract

The invention provides a hydrotalcite-based composite oxide catalyst, a preparation method and application of the hydrotalcite-based composite oxide catalyst in alkynol preparation, and solves the technical problems that an existing catalyst is complex in preparation, large in dosage and long in reaction time, the molecular formula of the catalyst is XxMg0.7-xAl0.2-yYyO, X is selected from any one of Ca, Sr and Ba, Y is selected from any one of Ga, In and Tl, 0.02 < = x < = 0.05, 0.02 < = y < = 0.05; the invention also discloses a preparation method of the catalyst and application of the catalyst in preparation of alkynol. The method can be widely applied to the technical field of organic chemicals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic chemical industry, and in particular to a hydrotalcite-based composite oxide catalyst, a preparation method and application thereof in the preparation of acetylene alcohols. Background Art

[0002] Alkynol (Structural Formula II below) is an important intermediate in the field of fine chemicals, mainly used in the production of vitamin E, vitamin A, pharmaceutical intermediates, synthetic fragrances, etc. In industry, alkynol is usually prepared by reacting carbonyl compounds (Structural Formula I below) with acetylene.

[0003] The general reaction formula is:

[0004]

[0005] Wherein, R1 and R2 are hydrogen or hydrocarbon groups.

[0006] In the prior art, the synthesis method of alkynols mainly focuses on the research of catalytic systems. For example, the Chinese invention patent with publication number CN116651451A discloses a catalyst and an acetylation method, which uses a modifier and a metal oxide catalytic system. Under the conditions of 3-10% catalyst dosage, 40-70° C. reaction temperature and 0.2 MPa reaction pressure, the reaction is carried out for 3-6 hours, and the carbonyl compound conversion rate can reach 99.6%, and the alkynol selectivity can reach 99.5%. However, the catalyst preparation of this method is relatively complex, the dosage is large, and there are technical problems such as long reaction time. Summary of the invention

[0007] The purpose of the present invention is to solve the deficiencies of the above-mentioned technology and provide a hydrotalcite-based composite oxide catalyst, a preparation method and its application in the preparation of acetylene alcohols, which has high yield, cheap catalyst, simple preparation, high stability, mild reaction conditions and short reaction time.

[0008] To this end, the present invention provides a hydrotalcite-based composite oxide catalyst, the molecular formula of the catalyst is X x Mg 0.7- x Al 0.2-y Y y O, wherein X is selected from any one of Ca, Sr, and Ba, Y is selected from any one of Ga, In, and Tl, 0.02≤x≤0.05, 0.02≤y≤0.05.

[0009] A preparation method of the hydrotalcite-based composite oxide catalyst comprises: dissolving soluble nitrates of X, Mg, Al and Y in water according to a stoichiometric molar ratio to obtain a metal nitrate mixed solution; mixing the metal nitrate mixed solution with a soluble inorganic alkali aqueous solution to obtain a suspension, and controlling the pH value of the suspension to be 9-10; subjecting the suspension to aging treatment in a water bath, filtering, washing and drying to obtain a catalyst precursor; and calcining the catalyst precursor to obtain the catalyst.

[0010] Preferably, the metal nitrate mixed solution and the soluble inorganic alkali aqueous solution are respectively added dropwise into distilled water to obtain a suspension, and the pH value of the suspension is adjusted to 9-10 by controlling the dropping speed; the suspension is aged in a water bath at 50-80°C, filtered, washed, and dried at 100-120°C to obtain a catalyst precursor; the catalyst precursor is calcined at 500-700°C to obtain the catalyst.

[0011] Preferably, the soluble inorganic alkali aqueous solution includes, but is not limited to, any one of a sodium carbonate aqueous solution, a sodium hydroxide aqueous solution, a sodium bicarbonate aqueous solution, and a potassium carbonate aqueous solution.

[0012] Preferably, the suspension is aged in a water bath at 50-80° C. for 10-15 h, dried at 100-120° C. for 8-12 h, and the catalyst precursor is calcined at 500-700° C. for 2-5 h.

[0013] An application of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols is to carry out an acetylation reaction between a carbonyl compound (the following structural formula I) and acetylene in the presence of the catalyst at a certain acetylene pressure and temperature. After the reaction is completed, the catalyst is filtered to remove the catalyst to obtain the acetylene alcohol (the following structural formula II). The reaction formula is as follows:

[0014]

[0015] Wherein, R1 and R2 are hydrogen or hydrocarbon groups.

[0016] Preferably, the carbonyl compound includes but is not limited to any one of acetone, 6-methyl-5-heptene-2-one, geranylacetone, butanone, 6-methyl-5-octen-2-one or phyton. The structural formulas thereof are as follows:

[0017]

[0018] After the acetylation reaction, the corresponding acetylenic alcohol compounds are: 2-methyl-3-butyn-2-ol, dehydrolinalool (3,7-dimethyl-6-octen-1-yn-3-ol), dehydronerolidol (3,7,11-trimethyl-6,10-dodecadiene-1-yn-3-ol), 3-methyl-pentyn-3-ol, dehydroethyllinalool (3,7-dimethyl-6-nonene-1-yn-3-ol), dehydroisophytol (3,7,11,15-tetramethyl-1-hexadecene-3-ol), and their structural formulas are as follows:

[0019]

[0020] Preferably, in the acetylation reaction, the mass percentage of the catalyst to the acetylenic alcohol is 0.5% to 2%.

[0021] Preferably, the acetylene pressure of the acetylation reaction is 0.1-0.5 MPa.

[0022] Preferably, the temperature of the acetylation reaction is 10-40° C., and the time of the acetylation reaction is 15-35 min.

[0023] Preferably, the acetylation reaction device is a loop reactor.

[0024] The present invention provides a hydrotalcite-based composite oxide catalyst and a preparation method thereof, and application of the catalyst in the preparation of acetylene alcohols by reacting a carbonyl compound with acetylene, and the beneficial effects are as follows:

[0025] (1) The catalytic efficiency of the present invention is high, the selectivity is good, the yield is as high as 99.3%, the conversion rate of carbonyl compounds is 99.7-99.9%, and the selectivity of alkynols is 99.6-99.8%.

[0026] (2) The present invention has high mass transfer efficiency and fast conversion rate, and the reaction time only requires 15 to 35 minutes.

[0027] (3) The present invention has mild reaction conditions, high safety and low reaction pressure.

[0028] (4) The catalyst used in the present invention is cheap and used in small amounts, thus reducing production costs.

[0029] (5) The catalyst of the present invention has good stability and maintains high performance after multiple batches are applied. After continuous application of 20 batches, the conversion rate fluctuates by ±0.2% and the selectivity fluctuates by ±0.2%. DETAILED DESCRIPTION

[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application. The methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercial products unless otherwise specified.

[0031] (I) Preparation of catalyst

[0032] Example 1

[0033] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.17 In 0.03 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.03:0.67:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.17 In 0.03 O, denoted as catalyst A.

[0034] Example 2

[0035] Hydrotalcite-based composite oxide catalyst Ca 0.03 Mg 0.67 Al 0.17 In 0.03 Preparation of O: Calcium nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Ca:Mg:Al:In = 0.03:0.67:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 50°C water bath for 15 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Ca 0.03 Mg 0.67 Al 0.17 In 0.03 O, denoted as catalyst B.

[0036] Example 3

[0037] Hydrotalcite-based composite oxide catalyst Ba 0.03 Mg 0.67 Al 0.17 In 0.03 Preparation of O: Weigh barium nitrate, magnesium nitrate, aluminum nitrate and indium nitrate according to the stoichiometric molar ratio of Ba:Mg:Al:In=0.03:0.67:0.17:0.03, add them into distilled water, mix them evenly under mechanical stirring, and drop the metal nitrate mixed solution and sodium carbonate aqueous solution into distilled water to obtain a suspension. The pH value of the suspension is 9-10 by controlling the dropping speed. The obtained suspension is aged in a water bath at 80°C for 10 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor is then calcined at 600°C for 4 hours to obtain the catalyst Ba 0.03 Mg 0.67 Al 0.17 In 0.03 O, recorded as catalyst C.

[0038] Example 4

[0039] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.17 Ga 0.03 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and gallium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:Ga=0.03:0.67:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 12 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.17 Ga 0.03 O, denoted as catalyst D.

[0040] Example 5

[0041] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.17 Tl 0.03Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and thallium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:Tl = 0.03:0.67:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 120°C for 8 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.17 Tl 0.03 O, denoted as catalyst E.

[0042] Example 6

[0043] Hydrotalcite-based composite oxide catalyst Sr 0.02 Mg 0.68 Al 0.17 In 0.03 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.02:0.68:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 500°C for 5 hours to obtain the catalyst Sr 0.02 Mg 0.68 Al 0.17 In 0.03 O, denoted as catalyst F.

[0044] Example 7

[0045] Hydrotalcite-based composite oxide catalyst Sr 0.05 Mg 0.65 Al 0.17 In 0.03Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.05:0.65:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 700°C for 2 hours to obtain the catalyst Sr 0.05 Mg 0.65 Al 0.17 In 0.03 O, denoted as catalyst G.

[0046] Example 8

[0047] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.18 In 0.02 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.03:0.67:0.18:0.02, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 110°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.18 In 0.02 O, denoted as catalyst H.

[0048] Example 9

[0049] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.15 In 0.05Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.03:0.67:0.15:0.05, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 10 hours, then filtered, washed, and dried at 100°C for 8 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 5 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.15 In 0.05 O, denoted as catalyst I.

[0050] Comparison of catalysts

[0051] Comparative Example 1

[0052] Hydrotalcite-based composite oxide catalyst Sr 0.01 Mg 0.69 Al 0.17 In 0.03 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.01:0.69:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.01 Mg 0.69 Al 0.17 In 0.03 O, denoted as catalyst J.

[0053] Comparative Example 2

[0054] Hydrotalcite-based composite oxide catalyst Sr 0.07 Mg 0.63 Al 0.17 In 0.03Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.07:0.63:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.07 Mg 0.63 Al 0.17 In 0.03 O, denoted as catalyst K.

[0055] Comparative Example 3

[0056] Hydrotalcite-based composite oxide catalyst Sr 0.07 Mg 0.63 Al 0.19 In 0.01 Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.07:0.63:0.19:0.01, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.07 Mg 0.63 Al 0.19 In 0.01 O, denoted as catalyst L.

[0057] Comparative Example 4

[0058] Hydrotalcite-based composite oxide catalyst Sr 0.07 Mg 0.63 Al 0.13 In 0.07Preparation of O: Sr nitrate, magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al:In = 0.07:0.63:0.13:0.07, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.07 Mg 0.63 Al 0.13 In 0.07 O, denoted as catalyst M.

[0059] Comparative Example 5

[0060] Hydrotalcite-based composite oxide catalyst Mg 0.7 Al 0.17 In 0.03 Preparation of O: Magnesium nitrate, aluminum nitrate and indium nitrate were weighed according to the stoichiometric molar ratio of Mg:Al:In = 0.7:0.17:0.03, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Mg 0.7 Al 0.17 In 0.03 O, denoted as catalyst N.

[0061] Comparative Example 6

[0062] Hydrotalcite-based composite oxide catalyst Sr 0.03 Mg 0.67 Al 0.2 Preparation of O: Sr nitrate, magnesium nitrate and aluminum nitrate were weighed according to the stoichiometric molar ratio of Sr:Mg:Al = 0.03:0.67:0.2, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and sodium carbonate aqueous solution were added dropwise to distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Sr 0.03 Mg 0.67 Al 0.2O, denoted as catalyst O.

[0063] Comparative Example 7

[0064] Hydrotalcite-based composite oxide catalyst Mg 0.7 Al 0.2 Preparation of O: Magnesium nitrate and aluminum nitrate were weighed according to the stoichiometric molar ratio of Mg:Al = 0.7:0.2, added to distilled water, and mixed evenly under mechanical stirring. The metal nitrate mixed solution and the sodium carbonate aqueous solution were added dropwise to the distilled water to obtain a suspension. The pH value of the suspension was controlled to be 9-10 by controlling the dropping speed. The obtained suspension was aged in a 60°C water bath for 12 hours, then filtered, washed, and dried at 100°C for 10 hours to obtain a catalyst precursor. The catalyst precursor was then calcined at 600°C for 4 hours to obtain the catalyst Mg 0.7 Al 0.2 O, denoted as catalyst P.

[0065] (II) Synthesis of alkynols

[0066] Application Example 1 A method for synthesizing 2-methyl-3-butyn-2-ol comprises the following steps:

[0067] 500g of acetone and 5g of hydrotalcite-based composite oxide catalyst A were put into a 1L loop reactor. The reaction was carried out for 20 minutes at an acetylene pressure of 0.3MPa and a reaction temperature of 30°C. The liquid product was analyzed by gas chromatography, and the acetone conversion rate was 99.9%, and the selectivity of 2-methyl-3-butyn-2-ol was 99.8%. The catalyst separated by filtration was continuously applied for 20 batches, and the conversion rate was 99.7-99.9%, and the selectivity was 99.6-99.8%, that is, the catalyst had good stability.

[0068] Application Examples 2 to 9, Comparative Application Examples 1 to 7

[0069] Application Examples 2 to 9 and Comparative Application Examples 1 to 7 are different from Application Example 1 in that the types of catalysts are different, and the other steps are the same. A reaction liquid is obtained, and a sample is taken for gas chromatography analysis to obtain the conversion rate of the raw material acetone and the selectivity of the product 2-methyl-3-butyn-2-ol. The results are shown in Table 1.

[0070] Please refer to Table 1, which is a summary of the experimental data and experimental results of Application Examples 1 to 9 and Comparative Application Examples 1 to 7.

[0071] Table 1 Summary of experimental data and experimental results of application examples 1 to 9 and comparative application examples 1 to 7

[0072]

[0073]

[0074] Experimental conclusion:

[0075] Comparing application examples 1 to 9, it can be seen that the hydrotalcite-based composite oxide catalysts prepared in Examples 1 to 9 of the present invention all have excellent catalytic activity, and can catalyze the raw material acetone and acetylene to carry out acetylation reaction to synthesize 2-methyl-3-butyn-2-ol, and realize the efficient synthesis of 2-methyl-3-butyn-2-ol, among which catalyst A has the best catalytic effect, the conversion rate of raw material acetone is as high as 99.9%, and the selectivity of product 2-methyl-3-butyn-2-ol is as high as 99.8%. Comparative application examples 1 to 4 use catalysts J, K, L, and M respectively change the element doping ratio, and the conversion rate and selectivity are slightly reduced. Comparative application example 5 uses catalyst N without doping at the Mg position, and Comparative application example 6 uses catalyst O without doping at the Al position. Comparative application example 7 uses catalyst P without doping at both the Mg position and the Al position, and the conversion rate and selectivity of comparative application examples 5 to 7 are significantly reduced.

[0076] Application Examples 10 to 17

[0077] The difference between Application Examples 10 to 17 and Application Example 1 is that the reaction parameters are different, and the other steps are the same. The reaction liquid is obtained, and a sample is taken for gas chromatography analysis to obtain the conversion rate of the raw material acetone and the selectivity of the product 2-methyl-3-butyn-2-ol. The results are shown in Table 2.

[0078] Please refer to Table 2, which is a summary of the experimental data and experimental results of Application Examples 1, 10-17.

[0079] Table 2 Summary of experimental data and experimental results of application examples 1, 10 to 17

[0080]

[0081]

[0082] Experimental conclusion:

[0083] Comparing application examples 1, 10 to 17, it can be seen that the four factors of ① reaction temperature, ② reaction pressure, ③ catalyst dosage, and ④ reaction time all have a certain influence on the reaction conversion rate and product selectivity. Overall, the carbonyl compound conversion rate and alkynol selectivity still reach a relatively high level.

[0084] Application Examples 18 to 27

[0085] The difference between Application Examples 18 to 27 and Application Example 1 is that the types of substrate carbonyl compounds are different, the reaction parameters are different, and the other steps are the same. The reaction liquid is obtained, and samples are taken for gas chromatography analysis to obtain the conversion rate of the raw material carbonyl compound and the selectivity of the product alkynol. The results are shown in Table 3.

[0086] Please refer to Table 3, which is a summary of the experimental data and experimental results of Application Examples 1, 18 to 27.

[0087] Table 3 Summary of experimental data and experimental results of application examples 1, 18 to 27

[0088]

[0089]

[0090] Experimental conclusion:

[0091] Comparing Application Examples 1, 18 to 27, it can be seen that the catalysts prepared in the embodiments of the present invention all have excellent catalytic activity, and can catalyze the acetylation reaction of different substrate carbonyl compounds with acetylene to synthesize the corresponding alkynols, thereby achieving efficient synthesis of alkynols. It can also be seen that the optimal reaction conditions suitable for different substrates are different.

[0092] It should be noted that in the above Examples 1 to 9 and Comparative Examples 1 to 7, in addition to the sodium carbonate aqueous solution, a soluble inorganic alkali aqueous solution such as a sodium hydroxide aqueous solution, a sodium bicarbonate aqueous solution, and a potassium carbonate aqueous solution can also be used instead, mixed with the metal nitrate mixed solution to obtain a suspension, and the pH value of the suspension is controlled to be 9 to 10. In addition, the water bath aging temperature and treatment time of the suspension, the drying temperature and time, and the roasting temperature and time can be adjusted according to actual conditions.

[0093] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A hydrotalcite-based composite oxide catalyst, characterized in that: The molecular formula of the catalyst is X x Mg 0.7- x Al 0.2-y Y y O, wherein X is selected from any one of Ca, Sr, and Ba, Y is selected from any one of Ga, In, and Tl, 0.02≤x≤0.05, 0.02≤y≤0.

05.

2. A method for preparing the hydrotalcite-based composite oxide catalyst according to claim 1, characterized in that: The preparation method of the catalyst comprises: According to the stoichiometric molar ratio, soluble nitrates of X, Mg, Al and Y are dissolved in water to obtain a metal nitrate mixed solution; the metal nitrate mixed solution is mixed with a soluble inorganic alkali aqueous solution to obtain a suspension, and the pH value of the suspension is controlled to be 9-10; the suspension is aged in a water bath, filtered, washed and dried to obtain a catalyst precursor; and the catalyst precursor is calcined to obtain the catalyst.

3. The method for preparing a hydrotalcite-based composite oxide catalyst according to claim 2, characterized in that: The metal nitrate mixed solution and the soluble inorganic alkali aqueous solution are respectively added dropwise into distilled water to obtain a suspension, and the pH value of the suspension is adjusted to 9-10 by controlling the dropping speed; the suspension is aged in a water bath at 50-80°C, filtered, washed, and dried at 100-120°C to obtain a catalyst precursor; the catalyst precursor is calcined at 500-700°C to obtain the catalyst.

4. The method for preparing a hydrotalcite-based composite oxide catalyst according to claim 3, characterized in that: The soluble inorganic alkali aqueous solution includes, but is not limited to, any one of a sodium carbonate aqueous solution, a sodium hydroxide aqueous solution, a sodium bicarbonate aqueous solution, and a potassium carbonate aqueous solution.

5. Use of the hydrotalcite-based composite oxide catalyst according to claim 1 in the preparation of acetylene alcohols, characterized in that: In the presence of the catalyst, at a certain acetylene pressure and temperature, the carbonyl-containing compound undergoes an acetylation reaction with acetylene. After the reaction is completed, the catalyst is removed by filtration to obtain the acetylenic alcohol.

6. Use of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols according to claim 5, characterized in that: The carbonyl compound includes, but is not limited to, any one of acetone, 6-methyl-5-heptene-2-one, geranylacetone, butanone, 6-methyl-5-octen-2-one or phyton.

7. Use of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols according to claim 5, characterized in that: In the acetylation reaction, the mass percentage of the catalyst to the acetylenic alcohol is 0.5% to 2%.

8. Use of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols according to claim 5, characterized in that: The acetylene pressure of the acetylation reaction is 0.1-0.5 MPa.

9. Use of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols according to claim 5, characterized in that: The temperature of the acetylation reaction is 10-40° C., and the time of the acetylation reaction is 15-35 minutes.

10. Use of the hydrotalcite-based composite oxide catalyst in the preparation of acetylene alcohols according to claim 5, characterized in that: The acetylation reaction device is a loop reactor.

Citation Information

Patent Citations

  • Catalyst and ethynylation process

    CN116651451A